2011
DOI: 10.1017/s1431927611012189
|View full text |Cite
|
Sign up to set email alerts
|

Compton Scattering Artifacts in Electron Excited X-Ray Spectra Measured with a Silicon Drift Detector

Abstract: Artifacts are the nemesis of trace element analysis in electron-excited energy dispersive X-ray spectrometry. Peaks that result from nonideal behavior in the detector or sample can fool even an experienced microanalyst into believing that they have trace amounts of an element that is not present. Many artifacts, such as the Si escape peak, absorption edges, and coincidence peaks, can be traced to the detector. Others, such as secondary fluorescence peaks and scatter peaks, can be traced to the sample. We have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
(11 reference statements)
0
3
0
Order By: Relevance
“…As Compton scattering is not an important phenomenon in most electron excited X-ray spectra, the model used in DTSA-II is fairly simplistic. Compton scattering can be observed (Ritchie et al, 2011) when small samples emitting higher energy (>10 keV) photons rest on low Z bulk substrates (like a particle on a carbon substrate). Compton scattering can also be observed in X-ray fluorescence spectra when the incident excitation X-rays scatter from the sample into the detector.…”
Section: Methodsmentioning
confidence: 99%
“…As Compton scattering is not an important phenomenon in most electron excited X-ray spectra, the model used in DTSA-II is fairly simplistic. Compton scattering can be observed (Ritchie et al, 2011) when small samples emitting higher energy (>10 keV) photons rest on low Z bulk substrates (like a particle on a carbon substrate). Compton scattering can also be observed in X-ray fluorescence spectra when the incident excitation X-rays scatter from the sample into the detector.…”
Section: Methodsmentioning
confidence: 99%
“…At present it is possible, similar to the common XRF or SEM/EDX spectra, to simulate XRF spectra with reliable scattering contributions , and evaluate before or even without the experiment, the chances of gaining more analytical information for any given individual experimental conditions. It was also recently reported that Compton scattering “artefacts”, easily misinterpreted as X-ray fluorescence peaks of trace elements, could be explained by such valuable simulations …”
mentioning
confidence: 99%
“…It was also recently reported that Compton scattering "artefacts", easily misinterpreted as X-ray fluorescence peaks of trace elements, could be explained by such valuable simulations. 23 ■ THEORETICAL BASIS OF X-RAY SCATTERING By irradiation of matter with an X-ray beam the following three types of interactions may occur: 24 (i) photoelectric absorption, (ii) elastic (or coherent, or Rayleigh) scattering, and (iii) inelastic (or incoherent, or Compton) scattering. The mass attenuation coefficient (MAC), which describes the attenuation degree of the X-rays in matter, is determined by all these three types of interactions.…”
mentioning
confidence: 99%